2010
DOI: 10.1007/s12602-010-9042-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Subtilosin Alone and Combined with Curcumin, Poly-Lysine and Zinc Lactate Against Listeria monocytogenes Strains

Abstract: In this paper, the antibacterial effects of the Bacillus amyloliquefaciens-produced bacteriocin subtilosin, both alone and in combination with curcumin, ε-poly-L-lysine (poly-lysine), or zinc lactate, were examined against Listeria monocytogenes. Results indicated that subtilosin inhibits both of the studied bacterial strains, Scott A (wild-type, nisin sensitive) and NR30 (nisin resistant). However, L. monocytogenes Scott A was more sensitive to subtilosin and pure curcumin. In addition, subtilosin was more ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…The third antimicrobial compound, polylysine, was previously demonstrated to synergize with both nisin and subtilosin against the food-borne pathogen Listeria monocytogenes (1,5), supporting the possibility of synergy with subtilosin against G. vaginalis. As previously described, an isobologram was constructed using the individual MICs of subtilosin and polylysine ( Table 1).…”
Section: Determination Of Micsmentioning
confidence: 87%
See 2 more Smart Citations
“…The third antimicrobial compound, polylysine, was previously demonstrated to synergize with both nisin and subtilosin against the food-borne pathogen Listeria monocytogenes (1,5), supporting the possibility of synergy with subtilosin against G. vaginalis. As previously described, an isobologram was constructed using the individual MICs of subtilosin and polylysine ( Table 1).…”
Section: Determination Of Micsmentioning
confidence: 87%
“…Considering the multitude of health risks associated with BV, ideally, there would be a low possibility of BV-associated organisms developing resistance to these new alternatives. The multiple-hurdle approach is therefore ideal, since it uses combinations of synergistic substances in concentrations lower than their individual effective doses (1). The use of more than one antimicrobial, especially those with differing mechanisms of action, makes it very difficult for the pathogen to overcome each "hurdle" and lowers the chances of significant numbers of cells surviving (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus ATCC 25923 strain. Bacteriocin subtilosin isolated from B. amyloliquefaciens in combination with encapsulated curcumin revealed partial synergism against wild-type and nisin sensitive strains of L. monocytogenes Scott A [48]. In another in vivo study using 500  μ g/disc of curcumin against clinical isolate of Staph.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…polylysine against the bacterial vaginosis-associated pathogen Gardnerella vaginalis [91][92][93]. Furthermore, it has been shown that the two-peptide lacticin 3147 synergistically interacts with polymyxin to inhibit Cronobacter spp.…”
Section: Bacteriocin Synergy In Combination With Other Bacteriocins Amentioning
confidence: 99%